Dynamics and the Problem of Recognition in Biological Macromolecules 1996
DOI: 10.1007/978-1-4615-5839-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Protein Dynamics

Abstract: Modem NMR has revltahzed the study of protein dynamics Multldlmenslonal spectra and the heteronuclear spectroscopy allow a substantial gam m resolution Dynamics can be analyzed at mdlvldual sites and data on segmental and sequence-dependent flexlblhty are accumulating This review summarizes the wide vanety of NMR approaches for observing mternal motions, mcludmg the folding processes, and the attempts to correlate dynamics to the blologlcal actlvlty of protems The lmphcatlons of mob&y on structure determmatlon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…We take up these two issues separately. In addition, we also show that folding times do not correlate with the energy gap ∆ CS restricted to the ensemble of compact structures as KS [2] desire. …”
mentioning
confidence: 75%
See 1 more Smart Citation
“…We take up these two issues separately. In addition, we also show that folding times do not correlate with the energy gap ∆ CS restricted to the ensemble of compact structures as KS [2] desire. …”
mentioning
confidence: 75%
“…We also demonstrated that there is "no useful correlation between folding times and the energy gap between the native conformation and the first excited state" [1]. In response to these results Karplus and Shakhnovich (KS) [2] try to argue (i) that the folding criterion used by KT is "essentially the same as one introduced earlier [3,4]" and (ii) that the energy gap used by KT is not "appropriate". We take up these two issues separately.…”
mentioning
confidence: 90%